Contributions of digital social research to develop Telemedicine in Calabria (Southern Italy): identification of inequalities in post-COVID-19 - Taddei, Luciana; Mendicino, Francesco; Grande, Teresa; Mulé, Antonella; Micozzi, Roberto; Parini, Ercole Giap (Frontiers in Sociology, 2023)
The paper discusses the role that sociology and digital social research methods could play in developing E-health and Telemedicine, specifically after the Covid-19 pandemic, and the possibility of dealing with new pandemics. In this article, we will reflect on an interdisciplinary research pilot project carried out by a team of sociologists, doctors, and software engineers at The University of Calabria (Italy), to give a proof of concept of the importance to develop Telemedicine through the contribution of digital social research. Furthermore, the application of digital social research has highlighted socioeconomic and cultural gaps that affect the perception of Telemedicine in the university community. The introduction describes the e-health context in Italy and Calabria, underlining strengths and weaknesses, as well as the role of digital social research and the definition of health inequalities. The second part covers the technological and methodological solutions adopted, the three questionnaires administered, and the type of data collected. We apply a web and app survey to administrate a structured questionnaire to a self-selected sample of the University Community. Finally, we discuss the results focusing on inequalities detected thanks to web and app surveys. In particular, we underline how gender, age, educational, and professional levels concern medical behaviors, and we reflect on the digital and cultural divide that characterizes the sample. There is often an unconscious involvement in Telemedicine, and an optimistic perception grows with age, education, professional, and income levels; equally important are the comprehension of digital texts and the effective use of Telemedicine. These key findings could help direct public and educational policies to reduce existing gaps and promote Telemedicine in Calabria.